(untitled) (Iraqi Journal of Medical Sciences, 2020)
Background:In prediabetes, neither individuals having diabetic range nor normal glycemic parameters in terms of fasting plasma glucose, impaired glucose tolerance or glycated hemoglobin. Two-thirds of those with prediabetes will ends eventually with type 2 diabetes. Early detection with the proper intervention will halt or reverse this progression. Data about prediabetes prevalence in Iraq are scarce. Objective:To estimate the prevalence of prediabetes among adults in Baghdad/Iraq and to identify socio-demographic and associated risk factors among the studied population and to evaluate glycated hemoglobin in the detection of prediabetes. Methods:This cross-sectional study enrolled adults (20-79 years) attending primary health care centers in Baghdad/Iraq for one year, those with known diabetes or on anti-diabetic drugs, pregnant women and those with other medical conditions that interfere with glycated hemoglobin level were excluded from the study. Data collected through direct interview. Anthropometric measurements and laboratory analysis after overnight fast were done to measure fasting plasma glucose, glycated hemoglobin and lipid profile. Results:Prediabetes prevalence was 20.6%. Prevalence was higher in older people (40-60 years) and individuals with overweight, obesity, and dyslipidemia, the agreement between fasting plasma glucose and glycated hemoglobin was very good. Conclusion:Prevalence of prediabetes in Iraq is higher than estimated and share the same risk factors to those with type 2 diabetes. Glycated hemoglobin compared to fasting plasma glucose, is a reliable test to screen for prediabetes in Iraq. Keywords:Prediabetes; intermediate hyperglycemia; glycated hemoglobin; Iraq Citation:Alogaily MH, Alsaffar AJ, Hamid MB. Prevalence of prediabetes among adults in Baghdad/Iraq. Iraqi JMS. 2019; 17(3&4): 215-222. doi: 10.22578/IJMS.17.3&4.8